The Quiet Revolution: A Feminist Analysis of Sudha Murty’s Dollar Bahu Through the Lens of Existentialism, Gynocriticism and Intersectional Theory - Menon, Prashasti; Thakur, Vibha Singh (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
This paper embarks on a feminist literary investigation of Sudha Murty’s novel Dollar Bahu, exploring its analysis of materialism, patriarchy and the evolving identity of women in modern India. By relating the existentialist framework of Simone de Beauvoir, the gynocritical lens of Elaine Showalter and the intersectional standpoints of Indian feminist scholars Nivedita Menon and Kumkum Sangari, this research paper argues that Sudha Murty’s apparently simple narrative delicately exposes the complex struggles of women narrowed by patriarchal structures. The analysis focuses on how the novel’s female characters, Gouramma, Vinuta and Jamuna, symbolize concepts of impermanence and transcendence, function within a distinct ‘female’ literary tradition and navigate the interconnecting oppressions of gender, class and family. Eventually, the paper demonstrates how Dollar Bahu serves as an influential microcosm for the silent revolutions shaping gender and social reorganization in modern Indian society.